WARS1 and SARS1: Two tRNA synthetases implicated in autosomal recessive microcephaly. Issue 10 (21st July 2022) - Bögershausen, Nina; Krawczyk, Hannah E.; Jamra, Rami A.; Lin, Sheng‐Jia; Yigit, Gökhan; Hüning, Irina; Polo, Anna M.; Vona, Barbara; Huang, Kevin; Schmidt, Julia; Altmüller, Janine; Luppe, Johannes; et al.
Abstract: Aminoacylation of transfer RNA (tRNA) is a key step in protein biosynthesis, carried out by highly specific aminoacyl‐tRNA synthetases (ARSs). ARSs have been implicated in autosomal dominant and autosomal recessive human disorders. Autosomal dominant variants in tryptophanyl‐tRNA synthetase 1 ( WARS1 ) are known to cause distal hereditary motor neuropathy and Charcot‐Marie‐Tooth disease, but a recessively inherited phenotype is yet to be clearly defined. Seryl‐tRNA synthetase 1 ( SARS1 ) has rarely been implicated in an autosomal recessive developmental disorder. Here, we report five individuals with biallelic missense variants in WARS1 or SARS1, who presented with an overlapping phenotype of microcephaly, developmental delay, intellectual disability, and brain anomalies. Structural mapping showed that the SARS1 variant is located directly within the enzyme's active site, most likely diminishing activity, while the WARS1 variant is located in the N‐terminal domain. We further characterize the identified WARS1 variant by showing that it negatively impacts protein abundance and is unable to rescue the phenotype of a CRISPR/Cas9 wars1 knockout zebrafish model. In summary, we describe two overlapping autosomal recessive syndromes caused by variants in WARS1 and SARS1, present functional insights into the pathogenesis of the WARS1 ‐related syndrome and define an emerging disease spectrum: ARS‐related developmental disorders with or without microcephaly. Abstract : Based on the identification of novel variants in aminoacyl‐tRNA synthetase (ARS) genes WARS1 and SARS1, the authors define an emerging disease spectrum related to all type 1 ARS genes: aminoacyl‐tRNA synthetase‐related developmental disorders with or without microcephaly (ARS‐DDM).